Integration of Education Planning Funds Base on Philanthropy: Drop Out School Mitigation - Saputra, Awang; Fauzi, Muhamad (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2022)
The increasing number of dropouts during the Covid-19 pandemic needs to find an alternative solution by planning for philanthropy-based education financing. This paper aims to discuss education financing planning and to know the role of philanthropy in rescuing dropout students. The research uses a qualitative method with a literature study approach with content analysis techniques. Educational institutions must plan education financing in the budget work plan by seeking alternative funding assistance for students dropping out of school due to economic problems. Mitigation of dropout students is carried out by identifying students and parents, providing counselling services, collaborating with donor agencies, continuing formal or non-formal schools and finding donors or sponsors. The role of philanthropy in Indonesia in education has provided positive support, equality and sustainability of the quality of human development, including dropout students. The research contribution provides an overview for educational institutions to find and prepare special budgets to overcome school financial difficulties and overcome students who leave due to not being able to carry out their financial obligations during the COVID-19 pandemic. The implication is that education financing planning efforts in mitigating dropouts are integrated into philanthropic institutions.